2020
DOI: 10.3389/fpsyt.2020.602524
|View full text |Cite
|
Sign up to set email alerts
|

Personal Recovery and Its Determinants Among People Living With Schizophrenia in China

Abstract: Objective: The past few decades have seen an evolution in the understanding of recovery from a clinical-based view that focuses on symptoms and functioning to a more consumer-oriented perspective that focuses on personal recovery. The present study aimed to assess personal recovery among people living with schizophrenia and determine its predictors.Methods: This cross-sectional study recruited a random sample of 400 people living with schizophrenia (PLS) from twelve community health centers of Hunan, China. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
1
10
1
Order By: Relevance
“…Functioning (global, social and vocational) were identified as predictors of personal recovery where better functioning at baseline was associated with higher levels of personal recovery at 2 years followup. Kukla et al (2014) also found that perceived socially functioning was the most significant predictor of personal recovery (Kukla et al, 2014) whilst a recent by Yu and colleagues found higher functioning was associated with personal recovery (Yu et al, 2020). The ability to engage in meaningful activity despite having mental health problems has regularly been associated with better prognosis and higher well-being for people with schizophrenia ; (Roosenschoon et al, 2019).…”
Section: Predictors Of Personal and Clinical And Recoverymentioning
confidence: 99%
“…Functioning (global, social and vocational) were identified as predictors of personal recovery where better functioning at baseline was associated with higher levels of personal recovery at 2 years followup. Kukla et al (2014) also found that perceived socially functioning was the most significant predictor of personal recovery (Kukla et al, 2014) whilst a recent by Yu and colleagues found higher functioning was associated with personal recovery (Yu et al, 2020). The ability to engage in meaningful activity despite having mental health problems has regularly been associated with better prognosis and higher well-being for people with schizophrenia ; (Roosenschoon et al, 2019).…”
Section: Predictors Of Personal and Clinical And Recoverymentioning
confidence: 99%
“…Evidence exists of a link between recovery, SWB, insight and functioning and mental disorders (Cannavò et al, 2016 ; Chan et al, 2018 ; Widschwendter et al, 2018 ; Yu et al, 2020 ). However, no previous studies have been known to address the innovative PMH construct and its correlation with this set of positive measures.…”
Section: Introductionmentioning
confidence: 99%
“…These findings match those of research conducted by Gathaiya, Mwaura, and Wagoro, (2018) (36) that reported that male schizophrenic patients had a double variety of relapses as compared to feminine patients. This may be incompatible with Yu et al (2020) (33) who reported that male was considerably and severally related to higher personal recovery. This discovery calls for more investigation into gender-based recovery studies and the mechanisms underlying the relation between gender and recovery in psychiatric patients.…”
Section: Discussionmentioning
confidence: 62%
“…Along with the same line, Yu et al (2020) (33) conducted a study entitled "personal recovery and its determinants among people living with schizophrenia in China" and found that patients' personal recovery was determined to be relatively low. This finding is in the same line with the results of Iasielloa, Agterena, Keyesd, and Cochrane (2019) (34) concluded that mentally ill patients who maintained the lowest level of positive mental health were less likely to recover from mental illness when compared to those who maintained the highest level of positive mental health.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation